Widefield, Spatiotemporal Mapping of Spontaneous Activity of Mouse Cultured Neuronal Networks Using Quantum Diamond Sensors - Price, Joshua Colm; Mesquita-Ribeiro, Raquel; Dajas-Bailador, Federico; Mather, Melissa Louise (Frontiers in Physics, 2020)
Quantum diamond sensors containing Nitrogen Vacancy (NV) centers were integrated into the culture of spontaneously electrically active cultures of live mouse primary cortical neurons. Two diamond formats were used enabling extracellular studies of cells cultured directly on a planar diamond plate and intracellular studies via endocytosis mediated integration of nanoscale diamond particles within cells. Over a 14 day culture period functional neuronal networks formed as confirmed by endogenous calcium transients detected via fluorescent imaging of a calcium probe (Fluo-5 AM). Spatially correlated images of photoluminescence from NV centers were also recorded demonstrating successful acquisition of optically detected magnetic resonance from regions of endogenously firing neuronal cultures. Further, a fast and simple measurement protocol based on acquisition of NV photoluminescence without and with the application of near resonant microwaves is presented. This protocol was applied to live signaling cells and dead cells. The relative photoluminescence from NVs with and without microwaves varied for the case of live as compared to dead cells warranting future investigation. Overall this work presents a protocol for integration of NV diamond sensors in a spontaneously active network of neuronal cells of relevance to the field of neuroscience. Photoluminescence from NV centers was detected with high spatiotemporal resolution using measurement protocols potentially capable of single shot detection of neuronal activity. It is anticipated that the methodologies introduced in this work will underpin the establishment of NV diamond sensors as a radically new measurement platform capable of rapid, non-destructive functional studies of cells.